Estimation of the Cytotoxic Effects of Yucca Gloriosa Variegata Leaves Extract on Albino Mice - Ansam Ghazi Abdulhalem; Hind Hussein Obaid (Indian Journal of Forensic Medicine & Toxicology, 2021)
Yucca gloriosa Variegata L. is a stemless. The whole plant of Y. gloriosa L. has vast medicinal uses. TheNative Americans and North New Mexico used a tea from the leaves and roots to treat asthma, headache,wound healing. As well as it was being consumed as daily dietary. All part of Y. gloriosa L. is rich in saponinsteroidal glycosides. Saponin extracts are well-known to be highly toxic. Hence, present study was carriedout to investigate the toxicity of saponin and estimate the LD50 value which helps in determining the safedose range for the drug that be used, as well as to determine hematological aspects and examine histologicaleffect. Different concentrations of saponin extract were injected into male mice (10,000, 8000, 6000, 4000,2000, 1600, 1200, 600, 300) mg/kg. The LD50 value of the saponin extract was estimated to be (3100mg/kg).Hematological study was assessed by using various hematological parameters like RBC, WBC, LYM, MID.Complete blood pictures of the treated mice indicated an evident leukocytosis and erythrocytopenia effectof the drug. Treated-mice kidney tissues specimens were examined microscopically indicated clear signs ofheavy inflammation, necrosis and swelling of renal tubes, degeneration of renal tubes as well as hyaline andhemorrhagic cast at high concentrations of leaves extract.